In-Vitro Antifungal Test of Methanol Extract of Butterfly Pea (Clitoria ternatea L.) Seeds Against Colletotrichum sp. the incitant of anthracnose of Red Chilli - Suganda, Tarkus; Amanda, Lauren Thalita; Maharani, Yani (CROPSAVER, 2023)
Colletotrichum sp. the incitant of anthracnose, is very detrimental disease in chili plants. Anthracnose control relies on synthetic fungicides that can have a negative impact on the environment and human health, so more environmentally friendly control alternatives are needed. The butterfly pea plant (Clitoria ternatea L.) is often used as a traditional medicine because it contains functional compounds that are antifungal and antibacterial. This study aimed to test the antifungal effect of the methanol extract of butterfly pea seeds against Colletotrichum sp. of chili plants. The research was carried out from February to April 2023 at the Phytopathology Laboratory of the Department of Pests and Plant Diseases, Faculty of Agriculture, Universitas Padjadjaran. The research method used was an experimental method with poison food techniques in a Completely Randomized Design consisted of 5 treatments with 5 replications. The treatment concentrations of extract used consisted of 1%, 2%, 3%, control, and fungicide mancozeb 0.2% as a comparison. The results showed that the methanol extract of butterfly pea seeds provided the highest inhibition of colony growth (34%) at a concentration of 3%. Inhibition of conidia production of 28.8% was shown at a concentration of 1% but no inhibition at concentrations of 2% and 3%. Methanol extract from butterfly pea seeds could not inhibit the germination of conidia of the fungus Colletotrichum sp. but the germinated conidia become aborted and fail to develop as miselia. The effectiveness of the methanol extract of butterfly pea seeds is still lower than the mancozeb fungicide.